(untitled) (Journal of Plant Disease Sciences, 2021)
Bacterial pustule disease of soybean caused by Xanthomonas axonopodis pv. glycines is the endemic disease on soybean crop in Vidarbha region of Maharashtra. The five plant extract sensitivity against pathogen was studied by paper disc method and bioagent efficacy evaluated by dual culture technique. Among the plant extracts, neem (7.97 mm) and karanj leaf extract (6.27mm) were found significantly superior over other plant extract in inhibiting the growth of the pathogen. In bioagents, Pseudomonas fluorescens was significantly superior to all treatments as showed maximum inhibition Bioagents,